Exploring the application of immunotherapy against HIV infection in the setting of malignancy: A detailed review article - Makuku, Rangarirai; Seyedmirzaei, Homa; Tantuoyir, Marcarious M; Rodríguez-Román, Eduardo; Albahash, Assil; Mohamed, Kawthar; Moyo, Ernest; Ahmed, Abdulrazaq Olamilekan; Razi, Sepideh; Rezaei, Nima (Elsevier, 2022)
According to the Joint United Nations Programme on HIV/AIDS (UNAIDS), as of 2019, approximately 42.2 million people have died from acquired immunodeficiency syndrome (AIDS)-related illnesses since the start of the epidemic. Antiretroviral therapy (ART) has significantly reduced mortality, morbidity, and incidence of the human immunodeficiency virus (HIV)/AIDS-defining cancers, taming once-dreaded disease into a benign chronic infection. Although the treatment has prolonged the patients’ survival, general HIV prevalence has increased and this increase has dovetailed with an increasing incidence of Non-AIDS-defining cancers (NADCs) among people living with HIV (PLWH). This is happening when new promising approaches in both oncology and HIV infection are being developed. This review focuses on recent progress witnessed in immunotherapy approaches against HIV-related, Non-AIDS-defining cancers (NADCs), and HIV infection